Race-related diversity experiences in lifelong learning: impacts on undergraduates' intercultural sensitivity and interracial bridging social capital - Tamam, Ezhar (Elsevier, 2012)
In this self-administered questionnaire survey the author determines the level of race-related diversity experiences and tests the hypotheses that there is a significant difference in the level of intercultural sensitivity and level of interracial bridging social capital across the different levels of race-related diversity experiences among undergraduates. The responses of 430 randomly selected students from three Malaysian race groups were analyzed. The results reveal a significant differential level of race-related diversity experiences across racial groups under study and support the hypothesized significant main effects for race-related diversity experiences on intercultural sensitivity and interracial bridging social capital among the students in all the three racial groups. A policy of race-related diversity engagement and inclusion should be firmly institutionalized at all levels of student activities to enhance intercultural sensitivity and interracial bridging social capital among the students.